Diagnosis and surgical treatment of the posterior knee instability - Glisić, Miodrag D; Blagojević, Zoran; Stevanović, Vladan; Ristić, Branko; Matić, Aleksandar (Vojnosanitetski pregled, 2020)
Background/Aim. Posterior cruciate ligament is the primary stabilizer of the posterior tibia translation and secondary stabilizer of external tibial rotation as well as varus, valgus knee angulation. It is the strongest ligament in the knee that hurts the rarest. The aim of this study was to show the indications for surgery, present the surgical technique and give results of surgical treatment of posterior knee instability. Methods. The study icluded 12 patients who were tretaed surgically for posterior knee instabilility at the Institute for Orthopaedic Surgery  “Banjica“, Belgrade, in the period from 1st January 2010 to 1st January 2014. All of them had arthroscopically assisted anatomic reconstruction of posterior crucuate ligament done with 4-strand hamstring tendon graft. Postoperative follow-up lasted approximately 42 months and Lysholm values and International Knee Documentation Committee (IKDC) score were compared as well  as the clinical status. Results. All treated patients had Grade III of posterior instability. Combined injuries of the posterolateral corner and anterior cruciat ligament (75%) were very frequent. Preoperative mean value of Lysholm score was 45.92 and postoperative 85.92 what was statistically significant improvement, the same as subjective IKDC score whose mean value was 38.58 preoperatively and 89.75 after the surgery and rehabilitation. Clinical examination showed better posterior knee stability although in 50% of patients certain level of instability remains. Conclusion.  Arthro-scopic reconstruction with 4-strand hamstring tendon gives satisfactory result with posterior cruciate ligament reconstruction. The result of subjective feeling of patient is much better then objective clinical examination. Although surgical procedure is technically demanding, with physically active patients having grade III of posterior instability it provides better result than non-surgical treatment.
Keywords: knee injuries; diagnosis; posterior cruciate ligament; orthopedic procedures; arthroscopy; treatment outcome